Case Report: The Use of Intravenous SMOFlipid Infusion to Treat Severe Asparaginase-Induced Hypertriglyceridemia in Two Pediatric Acute Lymphoblastic Leukemia Patients - Lau, Sie Chong Doris; Loh, C-Khai; Alias, Hamidah (Frontiers in Pediatrics, 2021)
Asparaginase-induced hypertriglyceridemia can have a spectrum of clinical presentations, from being asymptomatic to having life-threatening thrombosis or hyperviscosity syndrome. At present, there is no recommendation on routine lipid monitoring during asparaginase-containing treatment phase, nor a standardized guideline on its management. Two cases are presented here to illustrate the effects of concurrent infection on asparaginase-induced hypertriglyceridemia in patients with high-risk ALL and the use of SMOFlipid infusion as a treatment option in an acute situation.